2016
DOI: 10.2172/1257903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lower East Fork Poplar Creek Mercury Sources

Abstract: Thanks are also extended to Dr. Paul Ayers for his unique contribution to the analysis of bank soil fluxes; George Southworth for his contributions to early watershed modeling efforts; and Ami Riscassi and Carrie Miller, who took part in the first year of field work on the project. Maruthi Sridhar Balaji Bhaskar and Maria Martinez provided important contributions to the geospatial analyses, mapping, and data management activities. The authors also want to thank Wendy Hames and Tracy Clem for reporting and edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…At EFPC, sediments exhibit two zones of slightly higher Hg concentrations downstream from Y-12 (Brooks et al 2017). Previous studies have identified the importance of streambank erosional processes that contribute particle-bound Hg to the stream (Southworth et al 2010(Southworth et al , 2013Watson et al 2016Watson et al , 2017 but have not specifically examined how contaminant distribution in the streambank soils is related to the streambed sediments. The goal of this study is to better understand the distribution of Hg and MeHg in streambank soils and streambed sediments and to assess the potential for soils to serve as a source of contamination to streambed sediments.…”
Section: +mentioning
confidence: 99%
See 4 more Smart Citations
“…At EFPC, sediments exhibit two zones of slightly higher Hg concentrations downstream from Y-12 (Brooks et al 2017). Previous studies have identified the importance of streambank erosional processes that contribute particle-bound Hg to the stream (Southworth et al 2010(Southworth et al , 2013Watson et al 2016Watson et al , 2017 but have not specifically examined how contaminant distribution in the streambank soils is related to the streambed sediments. The goal of this study is to better understand the distribution of Hg and MeHg in streambank soils and streambed sediments and to assess the potential for soils to serve as a source of contamination to streambed sediments.…”
Section: +mentioning
confidence: 99%
“…EFPC is classified as an impaired water body because Hg levels in fish exceed the US EPA National Recommended Water Quality Criteria (NRWQC) and the state of Tennessee guidelines (both 0.3 mg kg −1 in fish tissue). A recent series of modelling studies found that the greatest flux of Hg is related to erosion of streambank soils during storm events, followed by inputs from Y-12 (Watson et al 2016(Watson et al , 2017. Streambank soil erosion rates ranged from 4 to 46 cm year −1 (Watson et al 2016).…”
Section: +mentioning
confidence: 99%
See 3 more Smart Citations